Teachers' Challenges in Teaching English to Students with Special Needs at SMP Negeri Hindu 2 Sukawati - Ni Made Yuniari; I Gusti Ayu Indah Triana Juliari; I Komang Dedik Susila; I Wayan Teguh Sastra Wiguna; I Wayan Gede Supawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2026)
Inclusive education ensures equitable access to quality education for all learners, including students with special needs, yet teachers face significant challenges in implementing effective English language instruction for these diverse learners. This study aimed to examine the pedagogical challenges teachers encounter when adapting English lessons for students with special needs, analyze how teachers address communication barriers, identify instructional strategies and accommodations used, and investigate classroom management challenges at SMP Negeri Hindu 2 Sukawati. Unlike previous research that broadly examines inclusive education, this study highlights the lived experiences of English teachers in a school without a formal inclusive program, offering a context-specific perspective often overlooked. A qualitative descriptive case study design was employed, utilizing purposive sampling to select 2-4 English teachers with direct experience teaching students with special needs. Data collection involved semi-structured interviews that analyzed through thematic analysis to identify recurring patterns and themes. The results revealed that teachers face multifaceted challenges including significant disparities in students' basic literacy abilities, inadequate specialized teaching materials and training, difficulties balancing attention between regular and special needs students, and disruptive behavioral management issues. Teachers demonstrated adaptive strategies such as multilingual instruction, differentiated learning approaches, modified assessments, and informal peer collaboration. However, professional development opportunities remained limited, with teachers relying primarily on spontaneous solutions and colleague discussions. The study concludes that while teachers show resourcefulness in addressing inclusive education challenges, systematic support systems, comprehensive training programs, and specialized resources are urgently needed. These findings provide important implications for inclusive education policy and practice by highlighting the necessity of formal teacher preparation programs, structured institutional support, and collaboration with special education experts to ensure that inclusive classrooms can effectively serve all learners.